Blood Beta-Amyloid and Tau in Down Syndrome: A Comparison with Alzheimer’s Disease - Lee, Ni-Chung; Yang, Shieh-Yueh; Chieh, Jen-Jie; Huang, Po-Tsang; Chang, Lih-Maan; Chiu, Yen-Nan; Huang, Ai-Chiu; Chien, Yin-Hsiu; Hwu, Wuh-Liang; Chiu, Ming-Jang (Frontiers in Aging Neuroscience, 2017)
Background: Changes in β-amyloids (Aβ) and tau proteins have been noted in patients with Alzheimer’s disease (AD) and patients with both Down syndrome (DS) and AD. However, reports of changes in the early stage of regression, such as behavioral and psychological symptoms of dementia (BPSD), in DS are sparse. Methods: Seventy-eight controls, 62 patients with AD, 35 with DS and 16 with DS with degeneration (DS_D), including 9 with BPSD and 7 with dementia, were enrolled. The levels of β-amyloids 40 and 42 (Aβ-40, Aβ-42) and tau protein in the blood were analyzed using immunomagnetic reduction (IMR). The Adaptive Behavior Dementia Questionnaire (ABDQ) was used to evaluate the clinical status of the degeneration. Results: The Aβ-40 and tau levels were higher and the Aβ-42 level and Aβ-42/Aβ-40 ratio were lower in DS than in the controls (all p < 0.001). Decreased Aβ-40 and increased Aβ-42 levels and Aβ-42/40 ratios were observed in DS_D compared with DS without degeneration (all p < 0.001). The ABDQ score was negatively correlated with the Aβ-40 level (ρ = −0.556) and the tau protein level (ρ = −0.410) and positively associated with the Aβ-42 level (ρ = 0.621) and the Aβ-42/40 ratio (ρ = 0.544; all p < 0.05). Conclusions: The Aβ-40 and Aβ-42 levels and the Aβ-42/Aβ-40 ratio are considered possible biomarkers for the early detection of degeneration in DS. The elevated Aβ-40 and tau levels in DS may indicate early neurodegeneration. The increased Aβ-42 in DS_D may reflect the neurotoxicity of Aβ-42. The paradox of the tau decreases in DS_D could be explained by a burnout phenomenon during long-term neurodegeneration. The different patterns of the plasma beta amyloids and tau protein may imply a different pathogenesis between DS with degeneration and AD in the general population, in spite of their common key pathological features.